INTERPRETASI KATA AL-ṢIRÂṬ AL-MUSTAQÎM DALAM ALQURAN: APLIKASI SEMANTIK TOSHIHIKO IZUTSU - Muhammad Anwar Idris (IAIN Syekh Nurjati Cirebon, 2020)
This paper tries to reveal the meaning of the word al-Ṣirâṭ al-Mustaqîm . As for the word al-Ṣirâṭ al-Mustaqîm and its derivations; as many as 33 well-known words in 21 surah in the Alquran. Of the many mentions of this word in the Quran, of course, it will have a different meaning. So it is necessary to study what exactly the meaning of al-Ṣirâṭ al-Mustaqîm in Alquran using the semantic theory of Toshihiko Izutsu. This theory explains the existence of the basic meaning and relational meaning of Pragmatics and paradigmatics and Weltanschauung (world of meaning) al-Ṣirâṭ al-Mustaqîm. The results of this study, that the word al-Ṣirâṭ al-Mustaqîm in Alquran has the basic meaning of